A consecutive case series analysis of a behavioral intervention for enuresis in children with developmental disabilities. (4th July 2018) - Lomas Mevers, Joanna; Muething, Colin; Call, Nathan A.; Scheithauer, Mindy; Hewett, Shannon
ABSTRACT: Children with developmental disabilities (DD) are more likely than typically developing peers to have issues with enuresis. Past research has shown the success of behavioral treatments consisting of scheduled sits and reinforcement for continent voids. However, this research has included small sample sizes, while studies with larger numbers have lacked key information (i.e., baseline rates and follow-up data to evaluate maintenance and generalization). The current study conducted a consecutive case series analysis of 44 individuals with developmental disabilities who completed a 2-week program for enuresis. Results showed significant improvement in continent voids and follow-up data suggested positive results maintained when treatment was implemented by caregivers in a home environment.